2019
DOI: 10.4049/jimmunol.1801405
|View full text |Cite
|
Sign up to set email alerts
|

MAIT Cells Upregulate α4β7 in Response to Acute Simian Immunodeficiency Virus/Simian HIV Infection but Are Resistant to Peripheral Depletion in Pigtail Macaques

Abstract: Mucosal-associated invariant T (MAIT) cells are nonconventional T lymphocytes that recognize bacterial metabolites presented by MR1. Whereas gut bacterial translocation and the loss/dysfunction of peripheral MAIT cells in HIV infection is well described, MAIT cells in nonhuman primate models are poorly characterized. We generated a pigtail macaque (PTM)-specific MR1 tetramer and characterized MAIT cells in serial samples from naive and SIV-or simian HIV-infected PTM. Although PTM MAIT cells generally resemble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(82 citation statements)
references
References 52 publications
6
58
2
Order By: Relevance
“…IFN-γ producing capacity was maintained, suggesting that there is a restoration of IFN-γ-producing MAIT cells in the blood ( Figure 3E). Recently, it has been shown that MAIT cells upregulate α4β7 (the gut homing integrin) during SIV infection in pigtail macaques (24); hence, we looked at the expression of α4β7 on RM blood MAIT cells during SHIV infection. Similar to the data on pigtail macaques, the expression of gut homing marker α4β7 was significantly higher on RM MAIT cells compared to non-MAIT cells post-SHIV infection ( Figure 3F).…”
Section: Mait Cells In Shiv-infected Macaques Are Highly Proliferativmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-γ producing capacity was maintained, suggesting that there is a restoration of IFN-γ-producing MAIT cells in the blood ( Figure 3E). Recently, it has been shown that MAIT cells upregulate α4β7 (the gut homing integrin) during SIV infection in pigtail macaques (24); hence, we looked at the expression of α4β7 on RM blood MAIT cells during SHIV infection. Similar to the data on pigtail macaques, the expression of gut homing marker α4β7 was significantly higher on RM MAIT cells compared to non-MAIT cells post-SHIV infection ( Figure 3F).…”
Section: Mait Cells In Shiv-infected Macaques Are Highly Proliferativmentioning
confidence: 99%
“…Similarly, MAIT cells have been shown to be reduced systemically in SIV-infected rhesus macaques (23). However, a recent study in SIV/SHIV-infected pigtail macaque, MAIT cells are shown to be increased in the blood (24). Results from these studies vary, and very few studies have been performed in rhesus macaques with SIV/SHIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is reasonable to assume that human MR1 tetramers can be used to characterize MAIT cells in other species. Nonetheless, species‐specific MR1 tetramers have been developed at least for mouse (Chen et al., ; Rahimpour et al., ) and macaque (Greene et al., ; Juno et al., ), and these represent superior reagents for analysis of MAIT cells in their respective species. Techniques described in this article are in part transferrable to studying macaque MAIT cells (Juno et al., ).…”
Section: Commentarymentioning
confidence: 99%
“…Nonetheless, species‐specific MR1 tetramers have been developed at least for mouse (Chen et al., ; Rahimpour et al., ) and macaque (Greene et al., ; Juno et al., ), and these represent superior reagents for analysis of MAIT cells in their respective species. Techniques described in this article are in part transferrable to studying macaque MAIT cells (Juno et al., ). Mouse models of disease have proven valuable for definitively assessing the role of MAIT cells in disease, described as part of Chen et al ().…”
Section: Commentarymentioning
confidence: 99%
“…We used Mauritian cynomolgus macaques (MCM), which have simplified major histocompatibility complex (MHC) genetics, for these studies. SIV-positive or -naïve MCM were infected with a low dose of Mtb for [12][13][14][15][16][17][18][19][20] weeks. While no difference in TB disease between the two cohorts was observed at 4 weeks post-Mtb infection [ 1 8 ] , at 8 weeks the SIV co-infected macaques had significantly more granulomas than the SIVnaïve macaques [ 1 8 ] .…”
Section: Introductionmentioning
confidence: 99%